Update on Chagas' disease in Mexico Actualización sobre la enfermedad de Chagas en México - Eric Dumonteil (Instituto Nacional de Salud Pública, 1999)
Chagas' disease, caused by the protozoan parasite Trypanosoma cruzi, represents a major public health problem in most of the American continent. As transmission of the parasite is being interrupted in most of South America, the disease remains endemic in various areas of Mexico. We review here some of the information gathered in recent years. Seroprevalence of T. cruzi infection in humans remains relatively high in some areas, and there has been a general increase in the number of chronic cases reported to health authorities in recent years. In fact, chronic chagasic cardiomyopathy appears to be affecting a large number of patients with heart disease, but many cases may be misreported because of the unspecific nature of the clinical symptoms. Epidemiological monitoring of vector and reservoir populations, as well as of human cases is helping focus on endemic areas, but a better coordination and development of these efforts is still needed. Recent studies of parasite biology are in agreement with previous work showing the great diversity of parasite characteristics, and support the need for a regional approach to this zoonosis. Strong and continuing support from health and academic authorities is thus still needed to further improve our understanding of Chagas' disease in Mexico and implement efficient control programs. La enfermedad de Chagas, causada por el parásito protozoario Trypanosoma cruzi, constituye un importante problema de salud pública en el continente americano. La transmisión del parásito se ha ido interrumpiendo en la mayor parte de América del Sur, pero la enfermedad sigue siendo endémica en varias regiones de México. En este artículo se revisa la información más reciente sobre dicha enfermedad. La seroprevalencia de la infección por T. cruzi se ha mantenido a niveles relativamente altos en algunas regiones, y se observa un aumento general en el número de casos reportados a las autoridades de salud en los últimos años. La cardiomiopatía chagásica crónica parece afectar a muchos pacientes con enfermedad cardiaca, pero aparentemente muchos casos no se reportan debido a la ausencia de especificidad del cuadro clínico. El monitoreo epidemiológico de las poblaciones de vectores y reservorios, así como de los casos humanos, contribuye a enfocar estudios en las zonas endémicas, pero se requiere de un mayor avance y coordinación de estos esfuerzos. Estudios sobre la biología del parásito coinciden con trabajos previos que demuestran la gran diversidad de las características del parásito, y apoyan la necesidad de estudios regionales de esta zoonosis. Es necesario un fuerte apoyo continuo por parte de las autoridades de salud y académicos para enriquecer nuestro conocimiento sobre la enfermedad de Chagas en México y desarrollar programas eficaces de control.